2017
DOI: 10.1038/nchembio.2312
|View full text |Cite
|
Sign up to set email alerts
|

An orthogonalized platform for genetic code expansion in both bacteria and eukaryotes

Abstract: In this study, we demonstrate the feasibility of expanding the genetic code of Escherichia coli using its own tryptophanyl-tRNA synthetase and tRNA (TrpRS-tRNA) pair. This was made possible by first functionally replacing this endogenous pair with an E. coli-optimized counterpart from Saccharomyces cerevisiae, and then reintroducing the liberated E. coli TrpRS-tRNA pair into the resulting strain as a nonsense suppressor, which was then followed by its directed evolution to genetically encode several new unnatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
152
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 125 publications
(157 citation statements)
references
References 35 publications
4
152
0
1
Order By: Relevance
“…9699 More recently, it has been demonstrated that a native Trp aaRS/tRNA pair in E. coli can be functionally replaced with a counterpart from yeast, and the liberated Trp pair can be used to encode ncAAs in bacteria. 86 Additionally, orthogonal aaRS/tRNA technologies have been used to incorporate ncAAs into proteins in mammalian cell lines at gm/L scale employing transient expression methods. 100-102 Viral vectors have allowed the ncAA machinery to be delivered efficiently into primary cells, as well as tissues, 96, 103, 104 where it was used among other applications to monitor voltage-sensitive changes in response to membrane depolarization events in neural cells.…”
Section: Expanding the Genetic Codementioning
confidence: 99%
“…9699 More recently, it has been demonstrated that a native Trp aaRS/tRNA pair in E. coli can be functionally replaced with a counterpart from yeast, and the liberated Trp pair can be used to encode ncAAs in bacteria. 86 Additionally, orthogonal aaRS/tRNA technologies have been used to incorporate ncAAs into proteins in mammalian cell lines at gm/L scale employing transient expression methods. 100-102 Viral vectors have allowed the ncAA machinery to be delivered efficiently into primary cells, as well as tissues, 96, 103, 104 where it was used among other applications to monitor voltage-sensitive changes in response to membrane depolarization events in neural cells.…”
Section: Expanding the Genetic Codementioning
confidence: 99%
“…Finally, it would be beneficial to develop orthogonal aaRS•tRNA pairs that can function across all domains, like the tRNA Pyl •PylRS pair (97). E. coli strains are being developed that replace the endogenous tRNA Tyr •TyrRS or tRNA Trp •TrpRS pairs with heterologous alternatives, thereby allowing the original pairs to be repurposed for ncAA incorporation (50, 52). …”
Section: Expanding the Genetic Code With Orthogonal Translation Systemsmentioning
confidence: 99%
“…The stage is set for developing a broader array of OTSs for physiologically relevant PTMs with an eye towards multi-site incorporation of different PTMs. The future of PTM chemical biology in this arena will require more recoding to reassign more codons as well as engineering new sets of OTS elements that can decipher various codons that are not cross-reactive 12,13 .…”
Section: Except After Cmentioning
confidence: 99%